2011
DOI: 10.1016/j.marenvres.2011.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of marine aquaculture at large spatial scales: Evidences from N and P catchment loading and phytoplankton biomass

Abstract: While several studies point at off-shore aquaculture as a possible source of impacts on the local marine environment, very few have analysed its effects at large scales such as at the bay, gulf or basin levels. Similar analyses are hampered by the multiple sources of disturbance that may concomitantly affect a given area. The present paper addresses these issues taking the Gulf of Castellammare (Southern Tyrrhenian Sea) as an example. Nitrogen (N) and phosphorous (P) loads were calculated for the period 1970e2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
1
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 51 publications
(42 reference statements)
0
40
1
4
Order By: Relevance
“…Modification of trophic status, for example increased nutrient concentration and phytoplankton biomass, was observed in a coastal embayment with a decadal history of aquaculture (Pusceddu et al 2009, Sarà et al 2011. Low density pearl farming can create a mutually beneficial environment for the growth of phytoplankton and pearl oysters, which has been examined in Gokasho Bay, Japan (Abo & Toda 2001).…”
Section: Changes In Bsi In Response To Pearl Farmingmentioning
confidence: 99%
See 1 more Smart Citation
“…Modification of trophic status, for example increased nutrient concentration and phytoplankton biomass, was observed in a coastal embayment with a decadal history of aquaculture (Pusceddu et al 2009, Sarà et al 2011. Low density pearl farming can create a mutually beneficial environment for the growth of phytoplankton and pearl oysters, which has been examined in Gokasho Bay, Japan (Abo & Toda 2001).…”
Section: Changes In Bsi In Response To Pearl Farmingmentioning
confidence: 99%
“…For example, Sarà et al (2011) found that nutrient and chlorophyll a concentrations in the Gulf Castellammare, Italy have been steadily increasing since the establishment of aquaculture facilities in 1999, although they had not reached a eutrophic status. In addition, hydrodynamic conditions at aquaculture sites are important for determining the rate of change.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] highlighted that the abundance of vibrios is often unrelated to that of faecal pollution indicators; therefore a complete assessment of the hygienic-sanitary quality of coastal waters should include these microorganisms to get a complete picture of the health risks associated to diseases from contaminated seafood. Halophilic vibrios are microorganisms autochthonous of marine environments; their abundance follows a seasonal trend, increasing during summer months [27]; moreover, coastal and estuarine habitats rich in organic polymers are typical habitats for vibrios whose growth depends on the availability of organic matter [11].…”
Section: Discussionmentioning
confidence: 99%
“…It is a wide bay about 70 Km long, comprised between Capo S. Vito and Terrasini, characterized by the presence of extensive mussel beds and by the outflows of alcohol distilleries which enrich waters with organic substrates; also stream inflows cause a persistent turbidity of waters, which have sporadically undergone to eutrophication. In spite of the great potentiality of the Gulf for aquaculture and fish farming, information on the microbiological conditions of the Gulf is still fragmentary; to our knowledge, only a few scientific reports are available [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Some of the most important documented effects of aquaculture comprise increase in organic matter contents and compositional changes of the sediment below fish cages, alteration of inorganic and organic chemistry of farm water and sediments, alteration of abundance, biomass and biodiversity of micro, meio and macro benthic communities and modification of distributional patterns of phytoplankton and microzooplankton abundance and production [75][76][77][78]. Although large-scale modification of the trophic status (i.e., nutrient concentrations and phytoplankton biomass) of marine areas has been described as a consequence of fish farming [75], most of the described impacts are confined to within 25 m up to 1 km distance [79,80].…”
Section: Fish Farmingmentioning
confidence: 99%